La Formación Docente: La Metáfora De La Caja Del Formador - Yolanda Márquez-Domínguez; Josué Gutiérrez-Barroso; Ana Isabel González-Herrera (European Scientific Journal, ESJ, 2018)
This paper focuses on the key training points needed to be a good teacher. Reflecting on the keys and elements of a good praxis often results to the assessment of training processes and the influence of these on good practices. The aim of this study titled “The Trainer’s Box” is to reflect on those elements which gaive specific answers that are adapted to the different objectives, contexts, and moments which have been generalized when speaking of “The New Teaching Role”, the “Ideal Teacher”, or the “Effective Teacher”. The starting point of this reflection is that there is not just one answer, nor a possibility of universal recommendations to the question as to what to include in the container. This, however, is in a bid to obtain an “ideal” formula on the subject of good teacher training.